2015
DOI: 10.1111/add.12880
|View full text |Cite
|
Sign up to set email alerts
|

Developmental progression to early adult binge drinking and marijuana use from worsening versus stable trajectories of adolescent attention deficit/hyperactivity disorder and delinquency

Abstract: Aims To examine the association between developmental trajectories of inattention, hyperactivity-impulsivity, and delinquency through childhood and adolescence (ages 8-16) and subsequent binge drinking and marijuana use in early adulthood (age 21). Design Prospective naturalistic follow-up of children with attention-deficit/hyperactivity disorder (ADHD) previously enrolled in a randomized controlled trial (RCT). Treatment-phase assessments occurred at 3, 9, and 14 months after randomization; follow-up assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
6
26
0
Order By: Relevance
“…Chassin and colleagues also reported more parental alcoholism, peer drinking, and drug use for adolescents whose binge drinking escalated rapidly. These risk factors, common for children with ADHD (Howard et al., ; Molina, Gnagy, Joseph, & Pelham, 2016), likely combine to reinforce SU after initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chassin and colleagues also reported more parental alcoholism, peer drinking, and drug use for adolescents whose binge drinking escalated rapidly. These risk factors, common for children with ADHD (Howard et al., ; Molina, Gnagy, Joseph, & Pelham, 2016), likely combine to reinforce SU after initiation.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the MTA data that risk for adult SU begins at a young age. Future analyses will consider the contribution of symptom persistence (Hechtman et al., ), the parallel unfolding of conduct problems that should exacerbate risk above those occurring in childhood (Howard et al., ), extended treatment effects (Swanson et al., ), and additional mediators and moderators suggested by the deepening literature on mechanisms of substance abuse risk in ADHD (e.g., Groenman et al., ; Molina & Pelham, ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that symptom persistence in adolescence is associated with other externalizing problems such as oppositional defiant disorder and conduct disorder, (i.e. Costello & Maughan, 2015), emotion problems, suicidality and academic failure and dropout (Costello & Maughan, 2015; Kessler et al, 2014), as well as early adult substance use (Howard et al, 2015) including, in this sample, an association between ADHD symptom persistence, delinquency, and frequency of alcohol use (Molina et al, 2012, and replicated in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of modest average increases over time summarizes a great deal of individual variability. Studies of symptom trajectories of children with ADHD show that about 25% to 30% exhibit a worsening pattern over time (Howard et al, 2015; Malone, Van Eck, Flory, & Lamis, 2010; Pingault et al, 2014; Swanson et al, 2007). In the present study, 27% of MTA probands persisted with clinically significant impairment before and after the transition out of high school, and impairments were most severe for the minority of adolescents with persistent externalizing comorbidity.…”
Section: Discussionmentioning
confidence: 99%